Influence of Friction Stir Process on Microstructure and Tensile Properties of LM28 Hypereutectic Al-Si Alloy - Abdulmalik, Samir Sani; Ahmad, Rosli (International Journal of Integrated Engineering, 2018)
This paper reports an investigation of the influence of friction stir processing (FSP) on the microstructure modification, tensile properties and hardness of as cast hypereutectic LM28 Al-Si alloy, aimed to decrease Si particles size, porosity, and enhancing tensile properties. Intense plastic deformation foisted by FSP resulted in a remarkable breaking up of the coarse eutectic and primary silicon particles into smaller ones, and closure of porosity. The area sizes of the fragmented Si particles decreased from 155.1 μm² to around 49.4 μm², aspect ratio of about 2.86 in the as cast condition decreased to around 1.63 after FSP. Porosity was also drastically reduced from 94 µm ECD, in the as cast condition to as low as 7.1 µm ECD. The strength and ductility of the alloy increased simultaneously after FSP. The increase in the tensile strength and ductility values after FSP, as compare to the as cast alloy was around 1.56, and 4.38 times respectively. The LM28 FS-processed alloy displayed an increase in quality index of around 1.97 times higher, than that of the as-cast alloy. The hardness of the alloy increased from 64.6HV for the as-cast alloy to about 85.74HV after FSP. Enhancement in all the properties was largely related to the pronounced changes of the shape, area size and distribution of the silicon particles along with the reduction of porosity FSP.